Įvardžiuotiniai būdvardžiai uteniškių tarmėje - Rinkauskienė, Regina (Kalbotyra, 2004)
The article deals with the pronominal adjectives of one of the East-Aukštaitian dialects. The material presents the historic development of the various forms. The formation and abundance of homonymic forms determine the use of the productive (i̯)a (f.(i̯ā) stems instead of the non-productive u (f.i̯ā) stem.